To find the expression for \( A \) that makes the equation \( A = 5 - \frac{11}{3} \) true, we first need to simplify \( 5 - \frac{11}{3} \).
First, we express \( 5 \) as a fraction with a denominator of \( 3 \):
\[ 5 = \frac{15}{3} \]
Now we can rewrite our equation as follows:
\[ A = \frac{15}{3} - \frac{11}{3} \]
Next, we perform the subtraction:
\[ A = \frac{15 - 11}{3} = \frac{4}{3} \]
Now we have \( A = \frac{4}{3} \). To find which expression corresponds to \( A = \frac{4}{3} \), we can simplify the given options:
-
Option 1: \( A = 1\frac{2}{3} + \frac{1}{3} \)
- \( 1\frac{2}{3} = \frac{5}{3} \)
- \( \frac{5}{3} + \frac{1}{3} = \frac{5 + 1}{3} = \frac{6}{3} = 2 \)
-
Option 2: \( A = 1\frac{2}{3} - \frac{1}{3} \)
- \( 1\frac{2}{3} = \frac{5}{3} \)
- \( \frac{5}{3} - \frac{1}{3} = \frac{5 - 1}{3} = \frac{4}{3} \)
-
Option 3: \( A = \frac{15}{3} + \frac{1}{3} \)
- \( \frac{15}{3} + \frac{1}{3} = \frac{15 + 1}{3} = \frac{16}{3} \)
-
Option 4: \( A = -1\frac{2}{3} + \frac{1}{3} \)
- \( -1\frac{2}{3} = -\frac{5}{3} \)
- \( -\frac{5}{3} + \frac{1}{3} = -\frac{5 - 1}{3} = -\frac{4}{3} \)
Now we compare our calculated \( A = \frac{4}{3} \) with the evaluated options. The only option that gives \( A = \frac{4}{3} \) is:
\[ \text{Option 2: } A = 1\frac{2}{3} - \frac{1}{3} \]
Thus, the answer is
\[ \boxed{1 \frac{2}{3} - \frac{1}{3}} \]